RNA interference as a tool for Euschistus heros (F., 1798) (Hemiptera: Pentatomidae) control - Rank, Aline Pereira (2020)
The expected increase in the world population demands greater production, efficiency and productivity. Agricultural pests are responsible for great losses in food production worldwide. So far, chemical control is the main strategy, but new, environmentally friendly strategies of pest control for the implementation of sound integrated pest management programs remains of a constant need. RNAi appears as a viable technology for controlling pests such as the bug Euschistus heros, which until now have restricted control methods. The technology itself is new and requires basic research in the optimization and implementation of more efficient methodologies, as well as information for correct data standardization and analysis. This study presents the analysis of five genes (Act - actin, ART - actin-related protein, Ef-1 - elongation factor 1, Hsp70 - heat shock protein 70, and 18s rRNA - 18S ribosomal RNA) for use in data normalization in RT-qPCR assays in E. heros. The analyzes were performed using the BestKeeper, Delta Ct, GeNorm and NormFinder platforms, and submitted to the RefFinder software for comparisons and final gene classification. The RefFinder software classified the Act and Ef-1 genes as the most stable for use when comparing instars, and the 18s rRNA and Act genes as the most suitable for tissue analysis of insects exposed to different nutritional conditions. We also investigated the genes involved in the RNAi pathway from an in-house transcriptome and selected four genes involved in key cellular events of insects as targets for RNAi. We describe the expression profiles of these genes in various tissues and during the growth of E. heros. We also tested different delivery strategies for double-stranded RNA (dsRNA) of the selected genes, and report insect mortality ranging from 40 to 60% depending on the selected target gene by dsRNA microinjection. We also demonstrate reduction in the mRNA abundance for all of the tested target genes, but the intensity of reduction was dependent on the target gene and the delivery strategy used. The data obtained are promising for the development of RNAi as an applied control strategy for E. heros.